Deficient public infrastructure and private costs: evidence from a time-use survey for the water sector in India - Lekha S. Chakraborty (Levy Economics Institute of Bard College, 2008)
This paper presents new evidence on the links between public-infrastructure provisioning and time allocation related to the water sector in India. An analysis of time-use data reveals that worsening public infrastructure affects market work, with evident gender differentials. The results also suggest that access to public infrastructure can lead to substitution effects in time allocation between unpaid work and market work. The broad conclusion of the paper is that public-investment policy can redress intrahousehold inequalities, in terms of labor-supply decisions, by supporting initiatives that reduce the allocation of time in nonmarket work.
Keywords: J22; H54; 330; Time Use; Public Infrastructure; Private Costs; Water Budgets